2015
DOI: 10.1111/1556-4029.12700
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Residues of Bone from Dissolving Human Remains in Acids

Abstract: Dissolving bodies is a current method of disposing of human remains and has been practiced throughout the years. During the last decade in the Netherlands, two cases have emerged in which human remains were treated with acid. In the first case, the remains of a cremated body were treated with hydrofluoric acid. In the second case, two complete bodies were dissolved in a mixture of hydrochloric and sulfuric acid. In both cases, a great variety of evidence was collected at the scene of crime, part of which was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 3 publications
3
16
0
Order By: Relevance
“…It is known that acid should be poured into water and not the other way around, in the case of sulfuric acid it is a strong exothermic reaction producing a lot of heat and fumes of explosive gases. Dutch research [75] confirms the experience of forensic experts that, in addition to macroscopic findings such as bone residues and artificial teeth, in both cases clear microscopic bone residues were found: (partially) digested bone, thin-walled structures and recrystallized calcium phosphate. Although some believe that the body can be completely dissolved in acid, at least some of these microscopic residues are always found.…”
Section: Discussionsupporting
confidence: 83%
“…It is known that acid should be poured into water and not the other way around, in the case of sulfuric acid it is a strong exothermic reaction producing a lot of heat and fumes of explosive gases. Dutch research [75] confirms the experience of forensic experts that, in addition to macroscopic findings such as bone residues and artificial teeth, in both cases clear microscopic bone residues were found: (partially) digested bone, thin-walled structures and recrystallized calcium phosphate. Although some believe that the body can be completely dissolved in acid, at least some of these microscopic residues are always found.…”
Section: Discussionsupporting
confidence: 83%
“…Based on XRF and EDS research, forensic researchers have found human bone and teeth to have predictable calcium to phosphorous (Ca/P) ratios which are measurable with very small samples, even those which are ancient, damaged, incinerated, or chemically treated. 1,[16][17][18][19] Ubelaker et al 16 used XRF to identify osseous and dental tissues using Ca/P ratios. They found that Ca/P ratios for osseous material calculated using weight percentage tend to be higher (1.82-1.95) than those reported by atomic weight (1.41-1.50).…”
Section: Acid Effects On Human Dentitionmentioning
confidence: 99%
“…Christensen et al 17 later validated the work of Ubelaker et al 16 in their XRF study of human and nonhuman osseous and dental samples, which included unaltered, burned, weathered, ancient, and chemically altered samples (nitric acid). Vermeij et al 1 conducted EDS analysis as part of a study of forensic case reports involving remains disposed in a mixture of different acids. They concluded the elemental presence of Ca and P was detected in small fragments after acid disposal where there was no macroscopically visibly identifiable human osseous or dental tissue.…”
Section: Acid Effects On Human Dentitionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a major development in new technological techniques in recent years that have produced powerful analytical tools in different areas of application. 1 In the forensic field, scanning electron microscopy (SEM)/energy dispersive X-ray (EDX) spectroscopy has attracted strong interest, especially, as it may be able to analyse inorganic traces left on the crime scene, both to provide clues regarding the nature of the weapon used (when it cannot be found) and the corpse which may have been moved, burned 2,3 or even dissolved in acid, 4 to divert investigation. Basically, this technique is applied to analyse gunshot residues, 5 to classify small glass fragments that may be present in different crime scenes, 6 to discover latent fingerprints on brass surfaces 7 and, finally, to make a comparative analysis of soil samples.…”
Section: Introductionmentioning
confidence: 99%